Stabilization and robustness analysis of multi-module impulsive switched linear systems. (November 2018) - Ai, Zidong; Peng, Lianghong
Abstract: In this work, a class of multi-module impulsive switched linear systems are formulated and their stabilization and robustness issues are studied. A pathwise state-feedback impulsive switching scheme is proposed and proven universal in sense that any asymptotically stabilizable impulsive switched linear system admits such a mechanism steering the system asymptotically stable. It is interesting to find that the designed scheme is flexible in avoiding Zeno phenomena and accommodating perturbations. That motivates us to conduct robustness analysis of the considered system under structural perturbations, unstructural perturbations and impulsive switching signal perturbations. Finally, a numerical example is provided to illustrate the effectiveness of the approach.